The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1tb00983d
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-specific vibration-based chiral differentiation of Raman spectra using cysteine modified gold nanoparticles: the cases of tyrosine and phenylalanine

Abstract: The chirality of amino acids plays a key role in many biochemical processes, and the development of spectroscopic analysis methods for chiral differentiation of amino acids is significant. Normal Raman...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…During the present study, amino acid capping was performed differently in the living body. Chirality-dependent properties of amino acids also influenced biochemical pathways in different ways [ 13 ]. Nanomaterials (NMs) also influenced the regulation of MTs in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…During the present study, amino acid capping was performed differently in the living body. Chirality-dependent properties of amino acids also influenced biochemical pathways in different ways [ 13 ]. Nanomaterials (NMs) also influenced the regulation of MTs in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al used Cys-modified gold NPs to identify tyrosine (Tyr) or Phe enantiomers. When the chiral configuration of Tyr or Phe was identical to that of Cys, the obtained Raman scattering signals were several times stronger than those with the opposite chirality, 70 allowing for widespread application of chirality-related detection with high specificity and sensitivity. It was observed that β-cyclodextrin-modified silver NPs aggregated in the presence of l -Tyr due to the preferential recognition with l -Tyr, 71 which resulted in the signal simplification of pulse voltammograms and can be used for chiral discrimination of tyrosine enantiomers.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Its circular dichroism is greater than phe. [172][173][174] In 2016, Gao et al briefly mentioned the concept of Cys self-assembly on the surface of Au or Ag via mercaptan group (SH) to obtain enantioselective GOxlike activity. [104] The results demonstrated that the presence of a chiral catalyst in a mixture of 0.2 times fructose, glycine, BSA and K + , Ca 2+ , Co 2+ , Zn 2+ , Pb 2+ , UA, AA, PA did not affect glucose detection.…”
Section: Amino Acid-functionalized Nmnzsmentioning
confidence: 99%